Climate-Smart Mapping and Adaptation Planning (CS-MAP): An introduction - Bernardo, Eisen (International Rice Research Institute, 2022)
The presentation introduced the Climate-Smart Mapping and Adaptation Planning (CS-MAP) as methodology to address climate-related risks that integrates various sources of information through participatory mapping and adaptation planning. The presentation covered the CS-MAP background, objectives, innovations, and limitations.